Independent validation of a new reirradiation risk score (RRRS) for glioma patients predicting post-recurrence survival: A multicenter DKTK/ROG analysis - Niyazi, Maximilian; Adeberg, Sebastian; Kaul, David; Boulesteix, Anne-Laure; Bougatf, Nina; Fleischmann, Daniel F.; Gruen, Arne; Kraemer, Anna; Roedel, Claus; Eckert, Franziska; Paulsen, Frank; Kessel, Kerstin A.; et al. (Radiotherapy and Oncology, 2018)
Background and purpose: Reirradiation (reRT) is a valid option with considerable efficacy in patients with recurrent high-grade glioma, but it is still not known which patients might be optimal candidates for a second course of irradiation. This study validated a newly developed prognostic score independently in an external patient cohort. Material and methods: The reRT risk score (RRRS) is based on a linear combination of initial histology, clinical performance status, and age derived from a multivariable model of 353 patients. This score can predict post-recurrence survival (PRS) after reRT. The validation dataset consisted of 212 patients. Results: The RRRS differentiates three prognostic groups. Discrimination and calibration were maintained in the validation group. Median PRS times in the development cohort for the good/intermediate/poor risk categories were 14.2, 9.1, and 5.3 months, respectively. The respective groups within the validation cohort displayed median PRS times of 13.8, 8.8, and 3.8 months, respectively. Uno's C for development data was 0.64 (CI: 0.60–0.69) and for validation data 0.63 (CI: 0.58–0.68). Conclusions: The RRRS has been successfully validated in an independent patient cohort. This linear combination of three easily determined clinicopathological factors allows for a reliable classification of patients and may be used as stratification factor for future trials.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Glioblastoma; High-grade glioma; Reirradiation; RRRS; Score